2007
DOI: 10.2165/00148581-200709001-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology Study of Bramitob??, a Tobramycin Solution for Nebulization, in Comparison with Tobi??

Abstract: In vitro performance of Bramitob((R)) was similar when nebulized with Pari TurboBoy k/LC Plus and Systam 290 LS nebulizers and comparable to that of TobiThe systemic bioavailability of tobramycin was similar after administration of either Bramitob or Tobi; however, in sputum samples the tobramycin peak concentration was slightly greater after administration of Bramitob than after Tobi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 13 publications
1
17
0
4
Order By: Relevance
“…Reduction in P. aeruginosa density has been reported in several studies [13,14,19,[74][75][76][77][78][79]. A clinical pharmacology study showed that peak sputum concentrations using tobramycin for nebulization were higher than the threshold for a significant antibacterial effect against P. aeruginosa (N400 µg/g) for two different tobramycin nebulizer formulations [79]. A review of randomized, controlled trials showed the benefit/efficacy of nebulized tobramycin, with no demonstrable adverse effects [80].…”
Section: Clinical Efficacymentioning
confidence: 95%
See 1 more Smart Citation
“…Reduction in P. aeruginosa density has been reported in several studies [13,14,19,[74][75][76][77][78][79]. A clinical pharmacology study showed that peak sputum concentrations using tobramycin for nebulization were higher than the threshold for a significant antibacterial effect against P. aeruginosa (N400 µg/g) for two different tobramycin nebulizer formulations [79]. A review of randomized, controlled trials showed the benefit/efficacy of nebulized tobramycin, with no demonstrable adverse effects [80].…”
Section: Clinical Efficacymentioning
confidence: 95%
“…Additionally, studies reported a reduction in the number of hospital admissions related to respiratory events [25,78,82,83] and reduced use of parenteral antibiotic treatment [14]. Reduction in P. aeruginosa density has been reported in several studies [13,14,19,[74][75][76][77][78][79]. A clinical pharmacology study showed that peak sputum concentrations using tobramycin for nebulization were higher than the threshold for a significant antibacterial effect against P. aeruginosa (N400 µg/g) for two different tobramycin nebulizer formulations [79].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Среднее время ингаляции составляет 15 мин, что на 30% меньше по сравнению с другими ингаляциями [35]. Препарат имеет длительные сроки хранения благо-даря высокой стабильности раствора: при температуре, не превышающей +8 °С -в течение 24 мес, при комнат-ной температуре -3 мес.…”
Section: обмен опытомunclassified
“…Более высокая концентрация раствора тобрамицина при ингаляции Брамитоба обеспечивает более быстрое и эффективное достижение терапевтических концентраций действующего вещества в секрете бронхов [35]. Высокий процент эрадикации синегнойной инфекции у больных МВ объясняется высокой антимикробной активностью препарата, подтвержденной значительным улучшением микробиологических показателей в сравнении с группой плацебо [36].…”
Section: обмен опытомunclassified
“…Therefore, new nebuliser systems have been investigated to improve tobramycin aerosol delivery to the peripheral airways and minimize residual drug wastage. Many in-vitro and in-vivo studies have been investigated to achieve these purposes [14][15][16][17][18][19][20][21][22][23][24][25][26][27] In-vivo studies the pharmacokinetic (PK) methods can provide accurate and reproducible quantification of drug delivery by measuring plasma levels to reflect lung deposition and bioavailability [28,29]. PK technique has been difficult to apply to most inhaled drugs, as the doses delivered are generally too small (microgram quantities), and the resulting plasma levels are low, which may be below the accurate detection limits of standard assays.…”
Section: Introductionmentioning
confidence: 99%